Performance and technology practices of virtual embodiment and interactivity - Broadhurst, Susan 1953-; Machon, Josephine 1979- (Macmillan Palgrave, 2011)
"This book, now in paperback, interrogates the interaction between new technologies and performance practice, linking the sensuous contact that exists between the physical and virtual, along with the resultant corporeal transformation. It features writings from international contributors specializing in digital art and performance practices."
Introduction : Body, space and technology / Susan Broadhurst and Josephine Machon -- Bodies without bodies / Susan Melrose -- Truth-seeker's allowance : digitising Artaud / Steve Dixon -- Transformed landscapes : the choreographic displacement of location and locomotion in film / John Cook -- Saira virous : game choreography in multiplayer online performance spaces / Johannes Birringer -- Artistic considerations in the use of motion tracking with live performers : a practical guide / Robert Wechsler -- Materials vs. content in digitally mediated performance / Mark Coniglio -- Learning to dance with angelfish : choreographic encounters between virtuality and reality / Carol Brown -- Kinaesthetic traces across material forms : stretching the screen's stage / Gretchen Schiller -- Sensuous geographies and other installations : interfacing the body and technology / Sarah Rubidge -- Body waves sound waves : optik live sound and performance / Barry Edwards and Ben Jarlett -- Intelligence, interaction, reaction, and performance / Susan Broadhurst -- The tissue culture and art project : the semi-living as agents of irony / Oron Catts and Ionat Zurr -- Addenda, phenomenology, embodiment : cyborgs and disability performance / Petra Kuppers -- Technology as a bridge to audience participation? / Christie Carson.
"First published 2006 in hardback."--Title page verso.
Includes bibliographical references and index.
Keywords: Technology and the arts; Digital art